Analysis of the Zakat Potential for the National Board of Zakat Republic of Indonesia - Farchatunnisa, Hidayaneu; Zaenal, Muhammad Hasbi; Hartono, Nono (International Journal of Zakat, 2023)
One of the important aspects in increasing zakat management is regarding the accuracy of the implementation of zakat collection strategies. As stated within the BAZNAS RI Strategic Plan Year 2020-2025, the main priority program to achieve the collection targets is through mapping the zakat potential based on the respective areas starting from the District/City levels, to the Provincial and finally National levels. Through utilizing the IPPZ measurement method, the zakat potential of BAZNAS RI which has been mapped in this study covers the following zakat objects: zakat on income of civil workers from ministries and government institutions, zakat on income of national corporate employees, zakat on income of TNI (the national army) and national police, zakat on income of BI and OJK employees, zakat on income of State-Owned Enterprises employees, ans zakat on income of DPR RI (House of People Representatives) members. The results of the measurement show that the total zakat potential of BAZNAS RI sums up to Rp 5,8 trillion.